H Hubungan Graviditas Trimester III dengan Tingkat Kecemasan Ibu Hamil dalam Menghadapi Tanda-Tanda Persalinan - Hasna Septiani, Firna; Zakiyah, Zakiyah; Mustikowati, Tri (Jurnal Kesehatan, 2020)
Abstact Gravidity is the frequency of pregnancy that pregnant women have experienced. Pregnancy is divided into 3 periods, namely the first trimester, second trimester and the third trimester. When pregnant, the mother has experienced anxiety. Anxiety increases in the lead up to primary labor in the third trimester. The purpose of this study was to determine the relationship of third trimester gravidity with the anxiety level of pregnant women in the face of signs of labor. This study used a descriptive correlation design with cross sectional approach. Data analysis using the Spearman Rank method. This research was conducted with 50 respondents using purposive sampling technique. The results showed an association between third-trimester gravidity and maternal anxiety level in the face of labor signs in the Cipinang Besar Utara North Jakarta Public Health Center with a correlation value (r = 0.411) with a p-value of 0.003 (p-value